2016
DOI: 10.1089/biores.2016.0022
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Coaxial and Emulsion Electrospinning Methods in the Field of Tissue Engineering

Abstract: Electrospinning has emerged as an effective method of producing nanoscale fibers for use in multiple fields of study. One area of significant interest is nanofiber utilization for tissue engineering because the nanofibrous mats can mimic the native extracellular matrix of biological tissues. A logical next step is the inclusion of certain molecules and compounds to accelerate or increase the efficacy of tissue regeneration. Two methods are under scrutiny for their capability to encapsulate therapeutic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 118 publications
0
52
0
Order By: Relevance
“…Studies in vivo and in vitro have shown that the nanofiber structure can absorb different growth factors and play a synergistic role in tissue growth. Coaxial electrospinning is a major advance in technology in the development of electrospinning [15][16][17]. The fibers prepared by this method not only have a high specific surface area and good mechanical properties, but they also have a unique core-shell structure, which can wrap biological molecules into nanofibers, maintain the activity of biological molecules, and achieve the purpose of carrying and sustained release.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vivo and in vitro have shown that the nanofiber structure can absorb different growth factors and play a synergistic role in tissue growth. Coaxial electrospinning is a major advance in technology in the development of electrospinning [15][16][17]. The fibers prepared by this method not only have a high specific surface area and good mechanical properties, but they also have a unique core-shell structure, which can wrap biological molecules into nanofibers, maintain the activity of biological molecules, and achieve the purpose of carrying and sustained release.…”
Section: Introductionmentioning
confidence: 99%
“…The produced scaffolds must have specific properties (physical, chemical and mechanical) to be fixable and compatible with human body. Different methods of electrospinning such as coaxial, triaxial and emulsion) used to produce nanofiber witch used in tissue engineering applications [134][135][136]. Pant et al produced nanofiber composite from (gelatin/nylon-6) and studied effect of gelatin concentration on the efficiency of the produced nanofiber and used the product as scaffold to tissue engineering [137].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Nanofibrous materials are currently being investigated for a variety of applications including tissue engineering because of their high surface area‐to‐volume ratio, flexibility, and mechanical properties such as tensile strength . Nanofibers are also utilized in scaffold design because they are considered to mimic the normal three‐dimensional (3D) extracellular matrix (ECM) of the cellular environment in tissues . The creation of 3D nanofiber polymer sheets can be accomplished through the process of electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning parameters include polymer solution viscosity, syringe pump flow rate, applied voltage, syringe‐to‐collector distance, and electrospinning chamber humidity . Reviews of the advances and applications of electrospun materials may be found in Huang et al and McClellan and Landis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation